Implementasi Pembuatan Konten Edukasi Kelistrikan bagi Masyarakat melalui Media Sosial Instagram PLN UID Jawa Timur - Alif Febriansyah; Ira Wikartika (Lembaga Pengembangan Kinerja Dosen, 2026)
The development of digital technology has encouraged the use of social media as a primary medium for delivering public service information. However, public understanding of electricity-related information, particularly regarding electrical safety and the utilization of digital services through the PLN Mobile application, remains limited. This community service activity aims to improve public literacy on electricity services through the creation and dissemination of educational content on the Instagram account of PLN Unit Induk Distribusi East Java. The methods applied include educational content planning, production of visual materials and informative narratives, and periodic content publication using a clear and accessible visual communication approach. The results indicate that Instagram-based electricity education content serves as an effective communication medium to convey PLN service information, enhance public awareness of electrical safety, and encourage the use of PLN Mobile digital features. This activity supports the digital transformation of public services and strengthens communication between PLN and the community.